Highly efficient synthesis of pyrimidine-5-carbonitrile derivatives over a robust biowaste bone char-Bronsted solid acid catalyst - Zahra Siahpour; Maryam Hajjami (Scientific Reports)
Abstract In this study, the conversion of bones (waste of food industry) into bone char is described. The presence of calcium phosphate and graphitic carbon gives bone char unique properties, with different possible uses. The catalytic behavior of bone char modified with chlorosulfonic acid is tested as reusable and eco-friendly solid acid biocatalyst in synthesis of pyrimidine-5-carbonitrile derivatives. The catalyst properties were characterized by different techniques such as FT-IR, BET, SEM, TEM, TGA, EDS and XRD. The bone char catalyst can be reused several times without reducing catalyst efficiency. In addition to the various reported benefits, the first use of bone char as a catalyst support for organic synthesis is an important novelty of this study.